2020
DOI: 10.1007/s12094-020-02394-8
|View full text |Cite
|
Sign up to set email alerts
|

100% peer review in radiation oncology: is it feasible?

Abstract: Purpose Peer review has been proposed as a strategy to ensure patient safety and plan quality in radiation oncology. Despite its potential benefits, barriers commonly exist to its optimal implementation in daily clinical routine. Our purpose is to analyze peer-review process at our institution. Methods and materials Based on our group peer-review process, we quantified the rate of plan changes, time and resources needed for this process. Prospectively, data on cases presented at our institutional peer-review c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…19 Similarly, a further study also highlighted daily conferences used for peer review amongst all treating ROs. 20 All cases (total of 148) were presented with an average session time of 38 min and majority of cases presented in 1-4 min. They found 80% of cases were acceptable and the most common reason for changes was contouring corrections (53.8%).…”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, a further study also highlighted daily conferences used for peer review amongst all treating ROs. 20 All cases (total of 148) were presented with an average session time of 38 min and majority of cases presented in 1-4 min. They found 80% of cases were acceptable and the most common reason for changes was contouring corrections (53.8%).…”
Section: Discussionmentioning
confidence: 99%
“…10 When contours are reviewed, issues with contouring account for over half of the major changes requested during peer review. 21,28 This indicates a potential mismatch between the focus of some current peer review practices and the clinically impactful 29 Reports suggest that participants are less likely to recommend changes to treatment plans once the patient has started treatment, likely due to an array of different cognitive biases and to avoid increasing workflow burden. 9,12,30 Even when changes are recommended, they are more likely to be implemented if treatment has not yet started.…”
Section: Guerrieri MD (Against)mentioning
confidence: 99%
“…There are examples in the literature of prospective peer review being successfully implemented, 12,14,21,28,53 as the opposition has indicated, but this is not the current standard in the field. Statistics presented in the literature within the last 10 yr indicate that less than 40% of treatment plans are reviewed prior to treatment start.…”
Section: Guerrieri MD (Against)mentioning
confidence: 99%
See 2 more Smart Citations